Peran Al-Qur’an dan Sunnah sebagai Sumber Hukum Ekonomi Syariah - Aura Lika Cahyani Andi Sufarid; Andi Maharani Erwin; Muhammad Ali Afsar; Kurniati Kurniati (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
The implementation of Islamic economics in the modern financial system is an effort to create an economic system that is fair, transparent, and sustainable, based on the principles taught in the Qur'an and Sunnah. The main principles of Islamic economics, such as the prohibition of riba (interest), fairness in transactions, zakat, the prohibition of gharar (uncertainty), and the balance in wealth distribution, provide a strong foundation for the formation of a more inclusive and social economic system. However, its implementation in the era of globalization faces various challenges, such as the lack of uniformity in Islamic legal standards across countries, differences in legal interpretations, and the integration of new technologies like fintech, blockchain, and cryptocurrency, which often conflict with Islamic principles. One solution that can be pursued is the development of Sharia-compliant digital financial products that adhere to the principles of fair and transparent transactions. On the other hand, Islamic financial institutions need to improve operational efficiency and strengthen the Sharia Supervisory Board (SSB) to ensure that financial products are in line with Sharia principles. Education and training in Islamic economics are also key to building a better understanding and accelerating the adoption of Islamic economic principles in the global financial system. Through close collaboration between Islamic financial institutions, regulators, and educational institutions, it is hoped that Islamic economics can provide a more ethical and sustainable alternative in the international market.